Foot strike patterns and running-related injuries among high school runners: a retrospective study - Goto, H.; Torii, S. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: There is a possible relationship between foot strike patterns and running-related injuries; however, this relationship among high school runners remains uninvestigated. Therefore, this retrospective cohort study examined this relationship among high school runners. METHODS: Overall, 123 male Japanese high school runners participated in this study and completed a questionnaire regarding their characteristics, running habits, and running-related injury histories. We filmed their habitual high-intensity training sessions from a lateral side. Participants` foot strike patterns were visually classified, and they were divided into the non-rearfoot strike (forefoot strike and midfoot strike) and rearfoot strike groups. An independent sample t-test or Welch`s t-test was used to compare participant characteristics, running habits, the number of running-related injuries in the past 1 year, and the running speed at the filmed training sessions between both groups. A Chi2 test was used to examine the relationship between running-related injury histories and foot strike patterns in both groups. RESULTS: The number of running-related injuries in the past 1 year was not significantly different between both groups; however, running-related injury incidence was significantly associated with non-rearfoot strike (P<0.05). Furthermore, non-rearfoot strike was significantly associated with a history of achillodynia (P<0.05). Other running-related injuries, such as medial tibial pain, lateral knee pain, and heel pain, were not significantly associated with foot strike patterns. CONCLUSIONS: Our study revealed that rearfoot strike runners did not have a higher risk of running-related injury compared to that of non-rearfoot strike runners, and that non-rearfoot strike was associated with achillodynia.